Depiction of Chamunda on the Antarala of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Chamunda, with twelve arms and standing atop a human body, is depicted on the bhadra (central projection) of the antarala (vestibule) of the Hazareshwar Temple. Her visage is characterized by skeletal features, dried saggy breasts, and a sunken belly adorned with a scorpion. She is draped in a triangular loin cloth and wears a jatamukuta (crown of matted hair) with a skull motif. Rounded earrings adorn her large earlobes, and serpents coil around her neck and ankles. In her right hand, she holds a trishula (trident), damaru (drum), arrow, a broken staff, and a ghanta (bell). Her left hands clasp a sarpa (snake) and a broken weapon. She holds a bowl in front. Below her, a seated human figure is depicted, drinking blood trickling from a severed head into a bowl.